The relationship between strategic management practices and the growth of Small and Medium Enterprises (SMEs) in Ghana - Alex Addae-Korankye; Bernard Agyei Aryee (Business: Theory and Practice, 2021)
The main goal of the study was to examine or investigate the impact of strategic management practices on the growth of SMEs in Ghana. Purposive sampling technique was employed to sample 190 SMEs in Accra, though 150 SMEs responded to the questionnaire. With the help of SPSS version 22, Multiple regression analysis was conducted to assess the impact of strategic management practices on the performance and hence growth of SMEs in Ghana. The study revealed a significant positive relationship between strategy formulation and growth of SMEs in Ghana. The study also found a significant positive relationship between strategy implementation and the growth of SMEs in Ghana, but found a negative relationship between strategy evaluation and growth of SMEs in Ghana. However, overall, the study found a positive relationship between effective and efficient application of strategic management practices and the growth of SMEs in Ghana. As a contribution to policy and practice, the study recommended among others that policy makers, managers and owners of Small and Medium Enterprises (SMEs) should employ strategic management experts especially in the field of strategy evaluation to enhance the quality of their strategy evaluation process so as to positively influence the performance and growth of SMEs.
Keywords: D2; M2; M1; L1; 650; growth; Small Medium Enterprises (SMEs); strategic management; strategy formulation; strategy implementa-tion; strategy evaluation